Carbon supported noble metal catalysts prepared by photochemical deposition - Faria, Joaquim (2010)
Photochemical deposition of noble metals in different supports is gaining importance because of its simplicity and advantages. Its main advantage is the ability of spreading very effectively the metal throughout the support, thus leading to very high dispersions, resulting in higher molecular control, with a positive effect on both activity and selectivity. This type of catalysts is important for industrial preparation of fine chemicals. A common synthetic route in these processes is the selective catalytic hydrogenation of organic substrates containing unsaturated functional groups, like steroids or α,β-unsaturated aldehydes.